PENGEMBANGAN INSTRUMEN EVALUASI STEM SKILLS PADA PEMBELAJARAN MATA KULIAH PENGELASAN TIG MIG - Aidil Adha; Farhan Yadi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to develop an evaluation instrument for STEM (Science, Technology, Engineering, and Mathematics) skills in TIG MIG welding courses in the Mechanical Engineering Education Study Program, Sriwijaya University. The background of this study is based on the need for a measuring instrument that is able to assess students' STEM skills comprehensively, especially in project-based learning that requires mastery of 21st century skills. The method used is research and development (Research and Development) with the ADDIE model consisting of five stages: analysis, design, development, implementation, and evaluation. The products developed include a performance assessment rubric, observation sheets, and self- and peer assessment instruments. The validity of the instrument was tested through expert judgment with three validators using the Aiken's V formula, while the reliability was tested through the SPSS application. The results of the study indicate that the evaluation instrument developed has met the valid and practical criteria for use in assessing students' STEM skills in TIG MIG welding practices. This instrument is expected to be a tool for lecturers in carrying out comprehensive and in-depth skill evaluations.